2016
DOI: 10.1590/1806-9282.62.03.269
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of perinatal outcomes in pregnant women with preterm premature rupture of membranes

Abstract: Objective: To determine the association between amniotic fluid index (AFI) and perinatal outcomes in preterm premature rupture of membranes (PPROM). Method: A retrospective cohort study was conducted between 2008 and 2012. 86 pregnant women were included, with a diagnosis of PPROM and gestational age from 24 to 35 weeks. Women who presented hypertensive disorders, diabetes, fetuses with birth defects and infection at admission were excluded. To determine the association between AFI and perinatal outcomes, chi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
5
18
0
4
Order By: Relevance
“…These findings are consistent with previous studies . Furthermore, the results from the present study revealed that oligohydramnios was a risk factor for neonatal mortality, which is consistent with two recent studies by Souza et al . and Mousavi et al .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These findings are consistent with previous studies . Furthermore, the results from the present study revealed that oligohydramnios was a risk factor for neonatal mortality, which is consistent with two recent studies by Souza et al . and Mousavi et al .…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, residual amniotic fluid after PPROM played a key role in neonatal outcomes, which were associated with an older delivery age, higher birth weight, and higher neonatal Apgar score. These findings are consistent with previous studies . Furthermore, the results from the present study revealed that oligohydramnios was a risk factor for neonatal mortality, which is consistent with two recent studies by Souza et al .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We have encountered patients with positive PPROM tests who maintain a normal amount of the amniotic fluid on ultrasound examination. The prognosis of these patients is better [22]. These patients are similar to patients experiencing PPROM as a complication of fetoscopic surgery.…”
Section: Pathologic Anatomical Remodelingmentioning
confidence: 76%